Visual search of illusory contours: Shape and orientation effects - Gvozdenović Vasilije (Psihologija, 2008)
Illusory contours are specific class of visual stimuli that represent stimuli configurations perceived as integral irrespective of the fact that they are given in fragmented uncompleted wholes. Due to their specific features, illusory contours gained much attention in last decade representing prototype of stimuli used in investigations focused on binding problem. On the other side, investigations of illusory contours are related to problem of the level of their visual processing. Neurophysiologic studies show that processing of illusory contours proceed relatively early, on the V2 level, on the other hand most of experimental studies claim that illusory contours are perceived with engagement of visual attention, binding their elements to whole percept. This research is focused on two experiments in which visual search of illusory contours are based on shape and orientation. The main experimental procedure evolved the task proposed by Bravo and Nakayama where instead of detection, subjects were performing identification of one among two possible targets. In the first experiment subjects detected the presence of illusory square or illusory triangle, while in the second experiment subject were detecting two different orientations of illusory triangle. The results are interpreted in terms of visual search and feature integration theory. Beside the type of visual search task, search type proved to be dependent of specific features of illusory shapes which further complicate theoretical interpretation of the level of their perception.